Implementation Of Accounting Information Systems And Internal Control Of Msme - Kurniawan, Ivan; Rachman, Helmy Aulia (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This research was conducted to design a cash receipt system and internal controls for Kartini Helm, which previously relied on a simple system and encountered several operational challenges. Before system design, it is essential to conduct an analysis based on the foundational Technology Acceptance Model to determine Kartini Helm's readiness to adopt the new system. This study utilizes a descriptive qualitative approach, drawing on primary and secondary data collected through observations, interviews, and documentation at Kartini Helm. The results indicate that the current cash receipt procedures at Kartini Helm lack structure, and data processing is neither sufficiently effective nor efficient. Implementing the proposed accounting information system for cash receipts will clarify the structure and responsibilities within each function, ensuring that data recording and storage processes are secure and systematically organized in line with established procedures.